Studi Komparatif Strategi Koping Adaptif VS Maladaptif Pengungsi Timur Tengah - Luthfiah Mawar; M. Agung Rahmadi; Helsa Nasution; Nurzahara Sihombing (Pusat Riset dan Inovasi Nasional, 2025)
This review analyzes 47 studies (N=12,487 refugees) published between 2010-2024 to compare the effectiveness of adaptive and maladaptive coping strategies in addressing trauma and stress among Middle Eastern refugees. The results of the analysis, utilizing a random effects model, affirm that adaptive coping strategies are positively correlated with psychological well-being (r = 0.62, p < 0.001) and social adjustment (r = 0.58, p < 0.001) of Middle Eastern refugees. Conversely, maladaptive strategies are associated with an increase in symptoms of depression (r = 0.45, p < 0.001) and anxiety (r = 0.52, p < 0.001). Furthermore, the moderator analysis reveals that social support enhances the positive effects of adaptive strategies (β = 0.34, p < 0.01). At the same time, trauma conditions exacerbate the negative impact of maladaptive strategies among refugees (β = 0.41, p < 0.001). Thus, these findings extend prior research by Alzoubi et al. (2019) and Paudyal et al. (2021), which focused solely on a single type of coping strategy, by providing insights into the complex interactions between various strategies and contextual factors affecting the coping mechanisms of Middle Eastern refugees as a novel contribution. Additionally, this research uniquely emphasizes, lacking in previous literature, that a combination of problem-focused and emotion-focused coping strategies can result in better adaptation outcomes for trauma-affected Middle Eastern refugees compared to the use of a singular strategy (d = 0.76, p < 0.001).